Question Prompt List as a Communication Tool for Adults With Gastroesophageal Reflux Disease: Incorporation of Patients' Perspectives. Issue 7 (14th August 2022) - Kamal, Afrin; Achkar, Edgar; Carlson, Dustin; Clarke, John; Fass, Ronnie; Gyawali, Chandra Prakash; Katzka, David A.; Patel, Dhyanesh; Penagini, Roberto; Rezaie, Ali; Roman, Sabine; Savarino, Edoardo; et al.
Abstract : Background: Question prompt lists (QPLs) are structured sets of disease-specific questions intended for patient use, enhancing the patient-physician communication by encouraging patients to ask relevant questions during a consultation. Recently, a preliminary 78 question gastroesophageal reflux disease (GERD) specific QPL was created by 12 esophageal experts through a modified Delphi (RAND/University of California, Los Angeles) technique. Patients' perspectives and opinions on each question, however, had not been accounted for in the preliminary expert' version. Aim: The aim was to modify a preliminary experts' QPL, specific to adults with GERD, following patient perspectives and opinions. Methods: A preliminary GERD QPL was modified through patient input and opinions. Thirty-eight patients with a clinical diagnosis of GERD followed at Stanford University Esophageal Clinic between January and November 2019 were consented to modify the preliminary 78 question expert QPL version. After receiving the QPL in Qualtrics (Provo, UT) by a direct e-mail invitation, patients independently rated questions on a 5-point Likert scale, where 1="should not be included, " 2="unimportant, " 3="don't know/depends, " 4="important, " and 5="essential." Questions were accepted for inclusion in the QPL with an a priori interagreement of 80% ranking in the range of 4 to 5. At the end, patients were encouraged to propose additional questions to incorporate into the QPL by open-endedly asking "Are there questions we didn't ask, that you think we should?" Results: Twenty-three patients with GERD (19 female, median age 64) fully participated and modified the existing QPL (60.5%). Of the 78 questions from the preliminary GERD QPL, 66 questions (84.6%) were accepted for inclusion. The question with the highest agreement among patients rating a question as essential consisted of "what habits, food, and drinks do I have to avoid?" (82.6%). Questions eliminated because of disagreement included "What is the natural history of GERD, " "Do I have a high chance to die from my Barrett's?, " and "Why are you prescribing an antidepressant to treat my GERD?" Nine patients suggested additional questions totaling to 16 separate questions, including "What type of surgeries are there to help GERD?, " "What stage is my GERD?, " "What are the odds/percentage of getting cancer from GERD?" Incorporating the suggested questions, the final GERD QPL—created by esophageal experts and modified by patients—consisted of 82 questions. Conclusion: Esophageal experts and GERD patients have a high level of agreement on important questions, though there is some variation in perspective. Future studies can simplify this list and measure the impact of a shared GERD QPL on patients' decisional conflict and perceived involvement in care.